(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the fundamental aspects of speech sound production, focusing on the articulatory and acoustic features that define human communication. It provides a clear explanation of the speech organs involved, such as the lungs, larynx, and vocal tract, and how they contribute to the articulation of different sounds. The article also covers key concepts like the manner and place of articulation, voicing, and the acoustics of speech, including frequency, amplitude, and formants.